PPARγ in Neuroblastoma. (19th May 2008) - Peri, Alessandro; Cellai, Ilaria; Benvenuti, Susanna; Luciani, Paola; Baglioni, Silvana; Serio, Mario
Abstract : Neuroblastoma (NB) is the most common extracranial tumor in children and accounts for around 15% of all paediatric oncology deaths. The treatment of NB includes surgery, chemotherapy, and radiotherapy. Unfortunately, most children with NB present with advanced disease, and more than 60% of patients with high-risk features will have a poor prognosis despite intensive therapy. Agonists of the nuclear receptor peroxisome proliferator-activated receptorγ (PPARγ ) have been shown to have pleiotropic effects, including antineoplastic effects. The studies that addressed the role and the possible mechanism(s) of action of PPARγ in NB cells are reviewed.